2017
DOI: 10.1002/chem.201700821
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of a Boron‐Doped Carbon‐Nanotube‐Supported Cu Catalyst for Selective Hydrogenation of Dimethyl Oxalate to Ethanol

Abstract: Heteroatom doping is a promising approach to improve the properties of carbon materials for customized applications. Herein, a series of Cu catalysts supported on boron-doped carbon nanotubes (Cu/xB-CNTs) were prepared for the hydrogenation of dimethyl oxalate (DMO) to ethanol. The structure and chemical properties of boron-doped catalysts were characterized by XRD, TEM, N O pulse adsorption, CO chemisorption, H temperature-programmed reduction, and NH temperature-programmed desorption, which revealed that dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 49 publications
0
23
0
1
Order By: Relevance
“…Ai et al. reported that suitable surface acidity could promote the hydrogenation of DMO . Furthermore, as mentioned above, it possessed large Cu NPs, a low dispersion, and a low copper surface area, as well as a low ratio of Cu + /(Cu + +Cu 0 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ai et al. reported that suitable surface acidity could promote the hydrogenation of DMO . Furthermore, as mentioned above, it possessed large Cu NPs, a low dispersion, and a low copper surface area, as well as a low ratio of Cu + /(Cu + +Cu 0 ).…”
Section: Resultsmentioning
confidence: 99%
“…可见, 复合载体, 并优化了载体掺杂比例 [19] , 或利用杂原子 掺杂等手段, 提升载体氧空穴数量 [23] . Li等 [21] 利用层 状类水滑石衍生的MnO [9,22,24,27] (网络版彩图) Cu-ZnO催化剂也在酯类加氢中表现出良好的催 化性能 [25,26] 碳纳米管 [29] 、石墨烯 [30] 等碳载体负载的或由金 属有机框架结构 [31] 经碳化衍生的铜基催化剂被应用 于酯加氢反应中. 载体空间限域结构及铜物种与碳载 体表面含氧官能团的相互作用有效促进了铜物种的分 散与稳定, 且多种碳载体或碳化过程均被报道存在铜 物种的自还原现象.…”
Section: 铜基催化剂载体、助剂的界面构建unclassified
“…Despite that Al 2 O 3 support has been used for widespread applications, the relatively high quantity of acid sites on Al 2 O 3 surface may catalyze unwanted isomerization or oligomerization reactions according to many studies ,,,. Therefore, in the present study, an inert SiO 2 support with a large surface was considered as a suitable choice ,…”
Section: Introductionmentioning
confidence: 99%
“…It is generally thought that Cu dispersion and/or the distribution of Cu 0 and Cu + species have great influence on the product selectivity during the hydrogenation process over Cu‐based catalysts . Tuning catalyst preparation parameters (e. g. promoters, Cu loading, calcination temperature) of Cu‐based catalysts is really efficient to modify Cu dispersion and Cu + /(Cu 0 +Cu + ) value. According to the previous literatures, it is plausible that both more dispersed Cu species and higher Cu + /(Cu 0 +Cu + ) value are effective to improve the product selectivity.…”
Section: Introductionmentioning
confidence: 99%